Discovering the benefits of water reuse in Middle East and North Africa - International Water Management Institute (International Water Management Institute, 2022)
Water can be used in cities and reused in agriculture, industries, and parks, with benefits for all. By cleaning and reusing water ecosystems thrive and we increase resilience to face climate change. Watch this video and join a growing coalition for more & safer water reuse in the Middle East and North Africa.